Scientific writing: following Robert Boyle’s principles in experimental essays -1704 and 1998 - Lareo Martín, Inés; Montoya Reyes, Ana (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2007)
Science and scientific method have evolved in parallel with changes in philosophical ideas. One aspect of the discipline affected by these changes is the way in which scientists' results should be shown to the world. However, it was not until the second half of the 17th century that the first recommendations or guidelines for reporting scientific discoveries appeared. The Royal Society became the first institution to concern itself with the form this new discourse should take. The aim of this paper is to analyse the linguistic evolution experienced by two pieces of scientific writing and to examine to what extent the two texts follow the recommendations of Robert Boyle and the Royal Society concerning the patterns scientific discourse should observe. Two texts were selected for the task, one published at the beginning of the 18th century, the other at the end of the 20th. For the purposes of comparison, the texts analysed are from the same discipline and both report an experiment on Optics.